Analysis Business Development to Improvement Micro, Small and Medium Enterprises Income in Lhokseumawe , Aceh - Yulianisah, Yulianisah; Audiya , Siti; Hamdani, Hamdani; Busra, Busra; Syarifudin, Syarifudin (ABEC Indonesia, 2024)
This study aims are to analyze influence development business , such as capital, location of business and innovation to improvement income of participating MSMEs in the SMEs Sunday Festival in Lhokseumawe City . This Research use quantitative method analysis with Structural Equation Modeling (SEM) using approach based on Partial Least Square (PLS). Research sample consists of 177 MSMEs on Sunday Lhokseumawe City Festival . Data collection techniques were carried out with purposive sampling method with sample that meets the requirements criteria certain. Research results show that indicators development business own significant influence​ to improvement SMEs income Except for the business location variable, all tested variables provide impact for development of MSMEs in Lhokseumawe City. The findings from study this expected can support effort sustainable and effective development of MSMEs in Lhokseumawe City , with focus on optimization factors that influence business success.